Case report: Streptococcus pneumoniae pneumonia characterized by diffuse centrilobular nodules in both lungs - Zhang, Fangqi; Qin, Shaowen; Xia, Fei; Mao, Congzheng; Li, Long (Frontiers in Medicine, 2023)
Background: Streptococcus pneumoniae (S. pneumoniae) is the most common pathogen in community-acquired pneumonia and takes the form of lobar pneumonia as typical CT findings. Varied patterns of radiological manifestation also have been reported in patients with S. pneumoniae pneumonia, however, the appearance of diffuse centrilobular nodules in both lungs is rarely reported. Case presentation: We report the case of a patient with a history of chronic lymphocytic leukemia for 9 years that presented with new-onset fever, cough, excess sputum, and shortness of breath for 1 week. He was given intravenous antibacterial (cephalosporin) treatment for 4 days, but his condition didn’t improve and dyspnea became more and more serious. The chest CT indicated diffuse centrilobular nodules in both lungs at admission. Patient’s bronchoalveolar fluid was sent for metagenomic next-generation sequencing, which only supported a diagnosis of S. pneumoniae infection. His condition improved gradually after antimicrobial treatment (moxifloxacin) and follow-up CT showed that the diffuse centrilobular nodules in both lungs absorbed completely. Conclusions: This case highlights a rare CT presentation of S. pneumoniae pneumonia that should alert clinicians, so as to avoid taking unnecessary treatment measures